Ruminal Fermentation of Anti-Methanogenic Nitrate- and Nitro-Containing Forages In Vitro - Anderson, Robin C.; Ripley, Laura H.; Bowman, Jan G. P.; Callaway, Todd R.; Genovese, Kenneth J.; Beier, Ross C.; Harvey, Roger B.; Nisbet, David J. (Frontiers in Veterinary Science, 2016)
Nitrate, 3-nitro-1-propionic acid (NPA) and 3-nitro-1-propanol (NPOH) can accumulate in forages and be poisonous to animals if consumed in high enough amounts. These chemicals are also recognized as potent anti-methanogenic compounds, but plants naturally containing these chemicals have been studied little in this regard. Presently, we found that nitrate-, NPA- or NPOH-containing forages effectively decreased methane production, by 35 to 87%, during in vitro fermentation by mixed cultures of ruminal microbes compared to fermentation by cultures incubated similarly with alfalfa. Methane production was further decreased during incubation of mixed cultures also inoculated with Denitrobacterium detoxificans, a ruminal bacterium known to metabolize nitrate, NPA and NPOH. Inhibition of methanogens within the mixed cultures was greatest with the NPA- and NPOH-containing forages. Hydrogen accumulated in all the mixed cultures incubated with forages containing nitrate, NPA or NPOH but was dramatically higher, exceeding 40 µmol hydrogen/mL, in mixed cultures incubated with NPA-containing forage but not inoculated with D. detoxificans. This possibly reflects the inhibition of hydrogenase-catalyzed uptake of hydrogen produced via conversion of 50 µmol added formate per mL to hydrogen. Accumulations of volatile fatty acids revealed compensatory changes in fermentation in mixed cultures incubated with the nitrate-, NPA- and NPOH-containing forages as evidenced by lower accumulations of acetate, and in some cases higher accumulations of butyrate and lower accumulations of ammonia, iso-buytrate and iso-valerate compared to cultures incubated with alfalfa. Results reveal that nitrate, NPA and NPOH that accumulate naturally in forages can be made available within ruminal incubations to inhibit methanogenesis. Further research is warranted to determine if diets can be formulated with nitrate-, NPA- and NPOH-containing forages to achieve efficacious mitigation in ruminant methane emissions without adversely affecting fermentative efficiency or risking toxicity to animals.